MacQsimal : Miniature Atomic vapor-Cells Quantum devices for SensIng and Metrology AppLication - (:unkn) unknown (My University, 2025)
Christoph Affolderbach (christoph.affolderbach@unine.ch) MacQsimal will design, develop, miniaturize and integrate advanced quantum-enabled sensors with outstanding sensitivity, to measure physical observables in five key areas: magnetic fields, time, rotation, electro-magnetic radiation and gas concentration. The common core technology platform for these diverse sensors is formed by atomic vapor cells realised as integrated microelectromechanical systems (MEMS) fabricated at the wafer level. The objectives of macQsimal are to develop five different types of miniaturized sensors: optically pumped magnetometers, atomic clocks, atomic gyroscopes, atomic GHz/THz sensors and imagers, and lastly, Rydberg-based gas sensors. It is the ultimate goal of macQsimal to develop scientific breakthroughs for atomic quantum metrology and sensing which will establish European leadership in the industry and drive excellence in quantum technologies in line with the strategic objectives of the FET Quantum Flagship.
Keywords: atomic clocks; vapor cells